Screening Degeneratif Disease Di Era Pandemi COVID-19 - Marwiati Marwiati; Ari Setyawati; M Fahrurozi (Karya Kesehatan Journal of Community Engagement, 2022)
Degenerative diseases are diseases that arise due to a decline in the function of body cells from their normal functions. Several degenerative diseases that appear are comorbid from the current pandemic. Health screening is carried out as a way to detect the presence of degenerative diseases so that they can be immediately prevented and make lifestyle improvements so that they do not cause the severity of infection during a pandemic. Some of the results obtained are an increase in blood pressure, an increase in uric acid levels in the blood, an increase in blood glucose levels and an increase in cholesterol in the blood. Education and lifestyle changes are expected to be able to prevent and overcome degenerative diseases so that they do not become comorbid in this pandemic.